PROVENTRICULUS AND GIZZARD IMPACTION IN EMU BIRDS - Jagatheesan, PN; Mahala, C; Kumar, P Senthil (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The emu farming is required more information on their husbandry and medical management for both producers and veterinarians. The present study describes impaction of proventricular - gizzard in emu chicks caused by ingestion of foreign materials.